IMPLEMENTASITASI KODE ETIK PUSTAKAWAN DALAM MENINGKATKAN KUALITAS KINERJA PELAYANAN PUSTAKAWAN DI BADAN PERPUSTAKAAN, ARSIP DAN DOKUMENTASI PROVINSI SULAWESI UTARA - Mbonuong, Risno (ACTA DIURNA KOMUNIKASI, 2013)
It in clear the library-man of library, Archives and Document section of Nort Sulawesi. Agree that the ethic code of library-man has to be applied for to enhance the quality performance service. How ever, the service is not yet enough according the expectator and needs of the library-man Keyword: Library-man, Service and Ethic Code